Hadith #705 - Sunan al-Nasa'i - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Aswad bin al-'Ala' bin Jaryh الأسود بن العلاء بن جارية; Amr bin 'Ali bin Bahr al-Bahli عمرو بن علي بن بحر الباهلي; Muhammad bin 'Abdur Rahman b. Abi Dh'ab محمد بن عبد الرحمن بن أبي ذئب; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan al-Nasa'i)
“When the Messenger of Allah (ﷺ) was on his deathbed, he had a Khamisah over his face. When his temperature rose, he would uncover his face. When his temperature rose, he would uncover his face. While he was like that he said: ‘May Allah curse the Jews and Christians, for they took the graves of their Prophets as places of worship.'”
Grade: